Participative Leadership Role in Applying professional Learning Communities in Secondary Schools in Al-Kharg Governorate - Alanazi, Nora Shnien; Darwish, Zainab Awad (Journal of Educational and Psychological Sciences, 2023)
The research aimed to identify the role of participative leadership in applying professional learning communities from respective of the teachers in secondary schools in Al-Kharg governorate. The researcher used the descriptive correlative survey method based on questionnaire, that was distributed to a random sample of (250) teachers. The most important results of the research were: The study sample members strongly agree on: the reality of applying of participative leadership in secondary schools with the total average of (3.79), and the reality of the areas were: the field of the “human relation” came first with an average (4.17), then the field of “motivation” with an average (3.77), the third field was “empowerment” with an average (3.74), the fourth field was “delegation of authority” with an average (3.73), and the last filed was “planning” with an average (3.58), the estimate of all fields were (large). The results also showed: The sample members strongly agree on reality of activating professional learning communities with an average of (3.70), and the role of participative leadership in the applying of professional learning communities in secondary schools with an average (3.71). and there were statistical significant differences at level (0.05) and less in the attitudes of the study sample members about the role of participative leadership in the applying of professional learning communities according to the gender variable in favor of females, according to the Qualification variable in favor of ’Bachelor or less’ category, and according to the Experience variable in favor of the category ’from 1 to less than 5 years’. The researcher recommended that research should continue on how to activate professional learning communities in the Kingdom’s schools.